Micronuclei induction in Rana catesbeiana tadpoles by the pyrethroid insecticide lambda-cyhalothrin - Campana, Marcela Alejandra (2003)
Pyrethroid lambda-cyhalothrin genotoxicity was evaluated using the micronucleus test in Rana catesbeiana tadpoles. The effects of concentration and exposure time on the micronuclei frequency were studied in blood smears obtained from tadpoles exposed to four concentrations (0.02, 0.1, 0.2 and 0.4 μg/L) of the compound for 24, 48, 72 and 96 h and 8, 15, 20 and 30 days. As a positive control, tadpoles were exposed to cyclophosphamide (5 mg/L). The micronucleated cell frequency was expressed per 1,000 cells. R. catesbeiana tadpoles exposed to increasing concentrations of lambda-cyhalothrin showed an increase in the micronuclei frequency in peripheral blood. Tadpoles exposed to cyclophosphamide (CP) also showed a significant increase in micronucleated erythrocytes which peaked after 15 days. These results suggest that R. catesbeiana tadpoles may provide a useful model for monitoring water pollution.